Penguatan Nilai-Nilai Kearifan Lokal Dalam Manajemen Pendidikan Berkarakter Sebagai Pondasi Dalam Pembelajaran Pada Siswa di MTs Nurul Fajri - Abdullah Idi; Mgs. Nazaruddin; Isnaini Isnaini; Ibrahim Ibrahim; Saipul Anwar; Hidayat Hidayat; Terisa Dea Putri; Rizky Nurfitri Lestari (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
The background of this research is to find out and analyze how to implement local wisdom-based character education management in developing local potential at MTs Nurul Fajri. This study uses a case study method with a type of qualitative research. Researchers use this type of qualitative research, because this type of qualitative research is a method that focuses on the involvement of the interpretation of researchers who try to interpret stakeholder behavior in a phenomenon that they experience. In this case, the application of local wisdom-based character education management in developing local potential at MTs Nurul Fajri shows that character education has such a big impact on stakeholders in the school environment. So that all stakeholders in the school environment are expected not only to learn and know about science, but also to be able to shape the personality of students who have character values based on local wisdom.